Postoperative communicating hydrocephalus following glioblastoma resection: Incidence, timing and risk factors - Hönikl, Lisa S.; Lange, Nicole; Barz, Melanie; Negwer, Chiara; Meyer, Bernhard; Gempt, Jens; Meyer, Hanno S. (Frontiers in Oncology, 2022)
Introduction: Glioblastoma (GBM) is the most common malignant primary brain tumor. Treatment includes maximally safe resection followed by radiation and / or chemotherapy. However, resection can lead to ventricular opening, potentially increasing the risk for development of communicating hydrocephalus (CH). Complications such as rebleeding and infection may also lead to CH and, eventually, the need for cerebrospinal fluid (CSF) diversion surgery. In this study, we evaluated the incidence of different types of hydrocephalus and potential risk factors for the development of CH following glioblastoma resection. Methods: 726 GBM patients who underwent tumor resection at our department between 2006 and 2019 were analyzed retrospectively. Potential risk factors that were determined for each patient were age, sex, tumor location, the number of resection surgeries, ventricular opening during resection, postoperative CSF leak, ventriculitis, and rebleeding. Uni- as well as multivariate analyses were performed to identify associations with CH and independent risk factors. Results: 55 patients (7.6%) needed CSF diversion surgery following resection surgery. 47 patients (6.5%) had CH, on median, 24 days after the last resection (interquartile range: 17-52 days). 3 patients had obstructive hydrocephalus (OH) and 5 patients had other CSF circulation disorders. Ventricular opening (odds ratio (OR): 7.9; p=0.000807), ventriculitis (OR 3.3; p=0.000754), and CSF leak (OR 2.3; p=0.028938) were identified as significant independent risk factors for the development of post-resection CH. Having more than one resection surgery was associated with CH as well (OR 2.1; p=0.0128), and frontal tumors were more likely to develop CH (OR 2.4; p=0.00275), while temporal tumors were less likely (OR 0.41; p=0.0158); However, none of those were independent risk factors. Age, sex, or rebleeding were not associated with postoperative CH. Conclusion: Postoperative CH requiring CSF shunting is not infrequent following GBM resection and is influenced by surgery-related factors. It typically occurs several weeks after resection. If multiple risk factors are present, one should discuss the possibility of postoperative CH with the patient and maybe even consider pre-emptive shunt implantation to avoid interruption of adjuvant tumor therapy. The incidence of CH requiring shunting in GBM patients could rise in the future.